2017
DOI: 10.1111/gbb.12401
|View full text |Cite|
|
Sign up to set email alerts
|

Polygenic risk for schizophrenia and neurocognitive performance in patients with schizophrenia

Abstract: Both neurocognitive deficits and schizophrenia are highly heritable. Genetic overlap between neurocognitive deficits and schizophrenia has been observed in both the general population and in the clinical samples. This study aimed to examine if the polygenic architecture of susceptibility to schizophrenia modified neurocognitive performance in schizophrenia patients. Schizophrenia polygenic risk scores (PRSs) were first derived from the Psychiatric Genomics Consortium (PGC) on schizophrenia, and then the scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 42 publications
(74 reference statements)
0
27
0
Order By: Relevance
“…Since attention is strongly impaired in individuals with SZ, most studies considered this domain in their analyses. Significant associations between SZ-PRS and attention are only reported by Nakahara et al [27] , while other studies did not reveal any significant association between SZ-PRS and attention [28,33] . Post hoc analysis by Xavier et al [35] revealed a significant association between SZ-PRS and vigilance but the finding did not survive correction for multiple testing.…”
Section: Attention/vigilancementioning
confidence: 94%
See 4 more Smart Citations
“…Since attention is strongly impaired in individuals with SZ, most studies considered this domain in their analyses. Significant associations between SZ-PRS and attention are only reported by Nakahara et al [27] , while other studies did not reveal any significant association between SZ-PRS and attention [28,33] . Post hoc analysis by Xavier et al [35] revealed a significant association between SZ-PRS and vigilance but the finding did not survive correction for multiple testing.…”
Section: Attention/vigilancementioning
confidence: 94%
“…In summary, most studies with affected individuals did not find an association between SZ-PRS and cognition i.e., general cognitive abilities, specific cognitive domains or intelligence quotient (IQ). Only a few were able to find an association for general cognitive abilities [27,33] and for specific cognitive domains [27,33] . The picture from studies in the general population is similarly blurry.…”
Section: What Have We Learned So Far?mentioning
confidence: 99%
See 3 more Smart Citations